Deradicalization-Based Aswajasi Education and Minagkabau Local Wisdom in Syaikh Sulaiman’s Thought - Muhammad Kosim; Martin Kustati; Duski Samad (IAIN Ponorogo, 2021)
Abstract: Religious radicalism can lead people to commit acts of violence in the form of physical and non-physical terror in the name of religious teachings. The actions can create a negative stigma about Islam in which has the nature of rahmatan lil 'alamin. One of the main causes for the emergence of religious radicalism is a narrow understanding of the religion. Therefore, religious radicalism needs to be anticipated by the deradicalization of education. The aim of the study is to analyze the thoughts of Sheikh Sulaiman Arrasuli, as one of the influential scholars in Minangkabau, focusing on the deradicalization through education based ASWAJASI and Minangkabau local wisdom. Although the term deradicalization of the education is not found in his books, his thoughts that juxtapose religious education and local wisdom of Minangkabau have relevance in efforts to deradicalize education. In his several writings, Sheikh Sulaiman Arrasuli argued that the deradicalization of education in Minangkabau was carried out by developing the understanding of Ahl al-Sunnah wa al-Jamā’ah wa Syafi’iyyah which is full of moderate and balanced teachings. In the educational process, teachers are required to have ulama-based competencies, who are ready to be role models and enlighteners for the umara, the importance of collaboration between ulama and umara, prioritizing tafaqquh fi al-din studies in madrasas, strengthening the morals of students who are devout and cultured, and implementing education without violence. The education process is based on religion and local wisdom.الملخص: يتسبب التطرف الديني في قيام شخص ما بارتكاب أعمال عنف ضد الإرهاب الجسدي وغير الجسدي باسم التعاليم الدينية. يخلق هذا العمل وصمة عار سلبية ضد تعاليم الإسلام التي هي رحمة للألمين. أحد دوافع ظهور الراديكالية الدينية هو الفهم الضيق للتعاليم الدينية. لذلك، يجب توقع التطرف الديني من خلال نزع التطرف عن التعليم. يهدف هذا البحث إلى تحليل أفكار الشيخ سليمان الرسولي، مع أنه باحثًا مؤثرًا في مينانغكابو، حول نزع التطرف عن التعليم في مينانغكابو. على الرغم من أن مصطلح إزالة التطرف في التعليم غير موجود في كتبه، فإن أفكاره التي تقارن التعليم الديني والحكمة المحلية لمينانغكابو ذات صلة بالجهود المبذولة لإزالة التطرف في التعليم. في العديد من كتاباته، وجد أن نزع التطرف في التعليم في مينانجكابو قد تم من خلال تطوير فهم أهل السنة والجماعة والسيافية المليء بالتعاليم المعتدلة والمتوازنة. في العملية التعليمية، يُطلب من المعلمين أن يكون لديهم كفاءات علمية على استعداد ليكونوا نماذج يحتذى بها ومستنير للحكومة، وأهمية التعاون بين العلماء والحكومة، ووتطرح الدراسات الدينية في المدارس، وتعزيز أخلاق الطلبة، وينفذون التعليم دون عنف. تستند عملية التعليم على الدين والحكمة المحلية.Abstrak: Radikalisme agama mengakibatkan seseorang melakukan tindakan kekerasan hingga teror fisik dan nonfisik dengan mengatasnamakan ajaran agama. Tindakan ini menimbulkan stigma negative terhadap ajaran Islam yang rahmatan lil ‘alamin. Salah satu pemicu munculnya radikalisme adalah pemahaman yang sempit terhadapa ajaran agama. Karena itu radikalisme tperlu diantisipasi dengan melakukan deradikalisasi pendidikan. Artikel ini bertujuan untuk menganalisis pemikiran Syekh Sulaiman Arrasuli, sebagai ulama berpengaruh di Minangkabau, tentang deradikalisasi melalui pendidikan berbasis ASWAJASI dan kearifan lokal Minangkabau. Meskipun istilah deradikalisasi pendidikan tidak ditemukan dalam kitab-kitabnya, akan tetapi pemikirannya yang menyandingkan pendidikan agama dan kearifan lokal Minangkabau, relevan dengan upaya deradikalisasi pendidikan. Dalam beberapa karya tulisnya, ditemukan bahwa deradikalisasi melalui pendidikan di Minangkabau dilakukan dengan mengembangkan paham ahl al-sunnah wa al-jamaah wa syafiiyyah yang sarat dengan ajaran moderat (tawasuth) dan seimbang (tawazun). Dalam proses pendidikan, guru dituntut memiliki kompetensi berbasis ulama yang siap menjadi teladan dan pencerah umat, pentingnya kolaborasi antara ulama dan umara, mengedepankan kajian tafaqquh fi al-din di madrasah-madrasah, menguatkan akhlak peserta didik yang taat beragama dan berbudaya, serta menerapkan pendidikan tanpa kekerasan. Proses pendidikan tersebut berbasis agama dan kearifan lokal.